Using the Artificial Gas Lift to Increase the Productivity of Noor Oil Field / Mishrif Formation - Salh, Talib A.; Sahi, Safaa H.; Ismael, Shaymaa A. Hussein (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Noor Oil Field is one of Iraqi oil fields located in Missan province / Amarah city. This field is not subjected to licensing rounds, but depends on the national effort of Missan Oil Company. The first two wells in the field were drilled in seventies and were not opened to production until 2009. The aim of this study is to study the possibility of using the method of gas lift to increase the productivity of this field . PROSPER software was used to design the continuous gas lift by using maximum production rate in the design. The design was made after comparing the measured pressure with the calculated pressure, this comparison show that the method of Beggs-Brill and Petroleum Expert2 gave the best results; therefore, these correlations have been adopted in the design of gas lift. The point of gas injection had been selected; the optimum gas injection rate, the maximum oil production rate, the number of valves required for gas injection and their depth, the pressure required to open and close each valve were calculated. The effect of water-cut, change the amount of ratio of gas to oil and decline reservoir pressure in natural flow case and gas lift method case were studied. The results of gas lift design show that the maximum oil production rate is (1000) STB/Day and the optimum gas injection rate (2.65) MM Scf/Day at using operating pressure of (1700) psi available at casing head and the minimum bottom hole following pressure is (1501.5) psi.